Time-intensity profile and relationship with consumer acceptability of processed cheese spread (Research, Society and Development, 2023)
Creamy “requeijão” is the commercially most prominent processed cheese spread in Brazil. The time intensity analysis is important to provide how the flavor behavior is for the consumers during the food ingestion and is used in order to obtain the temporal profile of an attribute in a certain product.  In the present study, three different commercial brands, leaders in the market, in their traditional and light versions, were subjected to sensory and instrumental evaluations. Time-intensity analyses and acceptance tests were carried out. After the statistical evaluation, applying ANOVA, the Tukey test (p. 0.05), Partial Least Square (PLS), it was concluded that the consumers preferred products with a more intense cheese flavor and higher adhesiveness, besides expressing a greater acceptance and purchase intention for the product in its traditional version.